Antisense Oligonucleotides Reduce RNA Foci in Spinocerebellar Ataxia 36 Patient iPSCs - Kosuke Matsuzono; Keiko Imamura; Nagahisa Murakami; Kayoko Tsukita; Takuya Yamamoto; Yuishin Izumi; Ryuji Kaji; Yasuyuki Ohta; Toru Yamashita; Koji Abe; Haruhisa Inoue (Elsevier, 2017)
Spinocerebellar ataxia type 36 is a late-onset, slowly progressive cerebellar syndrome with motor neuron degeneration that is caused by expansions of a hexanucleotide repeat (GGCCTG) in the noncoding region of NOP56 gene, with a histopathological feature of RNA foci formation in postmortem tissues. Here, we report a cellular model using the spinocerebellar ataxia type 36 patient induced pluripotent stem cells (iPSCs). We generated iPSCs from spinocerebellar ataxia type 36 patients and differentiated them into neurons. The number of RNA-foci-positive cells was increased in patient iPSCs and iPSC-derived neurons. Treatment of the 2'-O, 4'-C-ethylene-bridged nucleic acid antisense oligonucleotides (ASOs) targeting NOP56 pre-mRNA reduced RNA-foci-positive cells to ∼50% in patient iPSCs and iPSC-derived neurons. NOP56 mRNA expression levels were lower in patient iPSCs and iPSC-derived neurons than in healthy control neurons. One of the ASOs reduced the number of RNA-foci-positive cells without altering NOP56 mRNA expression levels in patient iPSCs and iPSC-derived neurons. These data show that iPSCs from spinocerebellar ataxia type 36 patients can be useful for evaluating the effects of ASOs toward GGCCTG repeat expansion in spinocerebellar ataxia type 36. Keywords: SCA36, iPSC, motor neuron, ASO, NOP56